(untitled) (Andamios, Revista de Investigación Social, 2024)
The territory of Mexico City is made up of Urban Land (UL) and Conservation Land (CL); the latter is intended to protect the ecosystem services of the City. The CL loses 0.8 km2 each year due to urban growth, causing environmental problems, including poor air quality and low water quality for agricultural use. Despite this problem, there are families that have preserved their plots in CL areas for generations by operating Family Agricultural Microenterprises (MEFA’s). The study analyzed, through case studies, the process of family succession in eight MEFA’s located in CL of five Municipalities. These studies were selected through grounded theory. The reported findings refer to the origin of the land ownership where the MEFA’s are located in 1880, the oldest and has been preserved by productive identity and family conviction; G2 provided environmental, economic, social, political and cultural viability through strategic movements to the MEFAs; however, the succession process between G2 and G3 is not yet in G2’s plans, a situation that puts the MEFAs and the SC at risk.